Synergism of multiple functional chromophores significantly enhancing the birefringence in layered non-centrosymmetric chalcohalides. Issue 6 (26th January 2021) - Huang, Junben; Cheng, Jianian; Lei, Bing-Hua; Wei, Zhonglei; Pan, Shilie; Yang, Zhihua
Abstract : Compared with one or two functional chromophores materials, Hg3 AsQ4 X (Q = S, Se; X = Cl, Br, I) with multiple ones generate extremely large birefringence due to the synergism of the d 10 cation Hg 2+, lone pair layer of As 3+ and mixed anions Q 2− /X − . Abstract : Large birefringence is important and indispensable for laser technology to meet the application demands. However, it is still a challenge to obtain optical materials with large birefringence that can extend the commercial birefringent crystals. Herein, we present a birefringence screening and analysis system to explore high-performance optical materials by introducing multiple functional chromophores. Using the high-throughput screening methodology, optical materials with one or two functional chromophores were explored. In particular, the chalcohalides Hg3 AsQ4 X (Q = S or Se; X = Cl, Br, or I) with multiple functional chromophores were screened out using the density functional theory and high-throughput screening method. The results show that Hg3 AsQ4 X (Q = S or Se; X = Cl, Br, or I) have an extremely large birefringence (Δ n : 0.391–0.493 at 1064 nm), two times that of the commercial birefringent crystal CaCO3 (0.172 at 1064 nm). And novel birefringent material motifs activated by the synergism of the d 10 cation Hg 2+, the layer of lone pair electrons of As 3+ cation, and the mixed anions Q 2− /X − (Q = S or Se; X = Cl, Br, or I) were found.